An analysis of seriousness, predictability and preventability of adverse drug reactions reported at a tertiary care teaching hospital in Kerala, India: a retrospective observational record based study - Shajahan, Jihana; Parathoduvil, Abdul Aslam; Purushothaman, Sangeetha (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Adverse drug reactions (ADR) are the leading cause of mortality and morbidity in all health care systems. Hospital based ADR monitoring and reporting programmes can throw some light upon the profile of ADRs and ways to prevent them, facilitating rational drug use. An attempt has been made in this study to analyse the seriousness, predictability, preventability, severity and outcome of ADRs occurring in a tertiary care hospital. Methods: This was a retrospective observational study based on the data collected from ADRs reported to an approved ADR monitoring centre (AMC). Data collected was evaluated for seriousness, predictability, preventability, severity and outcome using appropriate scales. Simple descriptive statistics was used for analysis. Results: The total number of ADRs reported was 300. Among this 39% reactions were serious. The commonest reason for considering as serious reaction was prolongation of hospitalization. The overall predictability was 40.4%. Total preventability was found to be 18.3%. Assessment of severity showed 55.3 %, 41.7%, 3% reactions in mild, moderate and severe grades respectively. 64.3% patients had recovered from the reaction and 30% were recovering at the time of reporting ADR. Only 0.3% ADRs caused death. Conclusions: Authors hope this study will foster the culture of reporting and analysing ADRs among health care professionals and students. The findings from the study can create awareness among health care professionals regarding the impact of ADRs on the treatment course.